UPAYA GURU DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN FIQIH - Rasman (UNISAN JURNAL, 2024)
The point of this exploration is to decide educators’ endeavors to expand understudies’ learning inspiration in class IX fiqh subjects at MTs Al-Ma’Arif. This exploration utilizes a subjective methodology, with a contextual investigation type, with a solitary case plan. Information assortment utilizes interview, perception and documentation methods. The information examination method utilizes enlightening investigation with an intuitive examination model. To check the legitimacy of the information, information triangulation was done. The aftereffects of the examination show that the educator’s endeavors to increment understudy learning inspiration in fiqh subjects are the instructor’s endeavors to increment understudy learning inspiration in fiqh subjects in Class IX MTs Al-Ma’Arif. In view of the examination results above, it tends to be reasoned that the educator’s endeavors to increment learning inspiration in fiqh subjects at MTs Al-Ma’Arif are by: Endeavors made by educators to build the learning inspiration of class IX understudies in fiqh subjects at MTs Al-Mama’ The illustration is that as follows: giving commendation, giving gifts, giving tests, giving discipline. The learning inspiration of class IX understudies in fiqh subjects at MTs Al-Ma’Arif should be feasible in light of the fact that understudies have signs of the endlessly want to succeed, the drive and have to learn, as well as expectations and dreams for what’s to come. Factors that impact the learning inspiration of class IX understudies in fiqh subjects at MTs Al-Ma’Arif are natural variables, in particular consolation from the actual understudies. Extraneous variables that come from the understudy’s current circumstance like support from guardians and the climate.